2014
DOI: 10.1111/jfd.12265
|View full text |Cite
|
Sign up to set email alerts
|

Infections of nervous necrosis virus in wild and cage‐reared marine fish from South China Sea with unexpected wide host ranges

Abstract: The concerns about the impact of the nervous necrosis virus (NNV) infections in wild fish have been raised. This paper presents the results of quarterly surveys of NNV in wild and cage-reared marine fish from South China Sea. Samples of 892 wild fish belonging to 69 species and 381 cage-reared fish belonging to 11 species were collected and were detected by seminested PCR and nested PCR. In the case of seminested PCR, the positive signal was detected in 3.0% and 3.1% samples of wild and cage-reared fish, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 16 publications
0
15
0
6
Order By: Relevance
“…In recent The RGNNV genotype, which affects tropical and temperate fish species, is the most widely distributed ( Figure 2) and has the highest number of susceptible species (Tables 1, 2 and 4). In recent years, surveys conducted in different geographical areas have shown that RGNNV is widely distributed Pathogens 2020, 9, 106 6 of 46 not only in farmed but also among wild fish in the Mediterranean basin and along the coasts of Asia and Australia [46,[62][63][64][65][66][67][68][69][70][71][72]. It has also been isolated from farmed white seabass (Atractoscion nobilis) in California [73].…”
Section: Geographical Distribution and Host Rangementioning
confidence: 99%
See 1 more Smart Citation
“…In recent The RGNNV genotype, which affects tropical and temperate fish species, is the most widely distributed ( Figure 2) and has the highest number of susceptible species (Tables 1, 2 and 4). In recent years, surveys conducted in different geographical areas have shown that RGNNV is widely distributed Pathogens 2020, 9, 106 6 of 46 not only in farmed but also among wild fish in the Mediterranean basin and along the coasts of Asia and Australia [46,[62][63][64][65][66][67][68][69][70][71][72]. It has also been isolated from farmed white seabass (Atractoscion nobilis) in California [73].…”
Section: Geographical Distribution and Host Rangementioning
confidence: 99%
“…It is well documented that changes experienced by ecosystems will affect the epidemiology of infectious diseases in animals, in the wild and under intensive farming conditions, including aquaculture [152][153][154][155][156]. The high number of wild asymptomatic species infected with NNV, mainly in Asian and Mediterranean countries [62,64,[66][67][68]71,80,82] and the quick rise in the viral load and subsequent outbreak of mortalities observed in experimentally infected sole when water temperature increased from 16 to 22 • C [148], suggest that VER outbreaks could have dramatic effects on natural populations, as has already been reported for some endangered fish species in the Mediterranean [72,96,109]. On the other hand, it could be argued that ocean warming could decrease the pathologies associated with the BFNNV genotype.…”
Section: Viral Thermotolerancementioning
confidence: 99%
“…; Liu et al . ). Following RGNNV infection, the interferon‐induced myxovirus resistance (Mx) proteins are upregulated in grouper cells (Chen et al .…”
Section: Introductionmentioning
confidence: 97%
“…Redspotted grouper nervous necrosis virus (RGNNV) is the main betanodavirus species that infect groupers (Chi et al 1997;Lai et al 2001;Tanaka et al 2003). RGNNV, which causes mass mortality (80-100%) in larvae and juveniles, has been a serious problem for farmed and wild groupers since 1994 (Chi et al 1997;Lai et al 2001;Gomez et al 2009;Bandin & Dopazo 2011;Vendramin et al 2013;Kara et al 2014;Liu et al 2015). Following RGNNV infection, the interferon-induced myxovirus resistance (Mx) proteins are upregulated in grouper cells (Chen et al 2006), and these proteins can inhibit viral propagation (Chen et al 2006;Lin et al 2006;Fern andez-Trujillo et al 2013;Wu, Kai & Chi 2013) by interacting with viral RNA-dependent RNA polymerase (RdRp) and coat protein (Chen et al 2008;Wu, Lu & Chi 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Viral encephalopathy and retinopathy is mainly observed in farmed fish, although severe outbreaks were reported in wild fish, mainly groupers (Gomez et al., ; Vendramin et al., ). Furthermore, asymptomatic betanodavirus infection has also been detected in wild fish (Baeck et al., ; Barker et al., ; Ciulli, Galletti, Grodzki, Alessi, Battilani, & Prosperi, ; Gomez, Baeck, Kim, Choresca, & Park, ; Gomez et al., ; Liu et al., ; Panzarin et al., ). The occasional presence of betanodaviruses in invertebrates was detected in the Mediterranean Sea, South Korea and Japan (Ciulli, Grodzki, Bignami, Serratore, & Prosperi, ; Fichi et al., ; Gomez, Baeck, Kim, Choresca, & Park, ; Gomez, Mori, Okinaka, Nakai, & Park, ; Gomez et al., ; Panzarin et al., ).…”
Section: Introductionmentioning
confidence: 99%